Nationalism and modernism : a critical survey of recent theories of nations and nationalism - Smith, Anthony D. (Routledge, 1998)
The first major study in over three decades to explore the essential arguments of all the major theoretical interpretations of nationalism, from the modernist approaches of Gellner, Nairn, Breuilly, Giddens and Hobsbawm to the alternative paradigms of van den Bergh and Geertz, Armstrong and Smith himself. In a style accessible to the student and the general reader Smith traces the changing view of this hotly discussed topic within the current political, cultural and socioeconomic arena. He also analyses the contributions of such historians, sociologists and political scientists as Seton-Watson, Reynolds, Hastings, Horowitz and Brass. The survey concludes with an analysis of post-modern approaches to national identity, gender and nation, making it indispensable reading to all those interested in gaining full and authoritative knowledge of nationalism.
Keywords: Nationalism.; International relations.; Nationalisme.; Relations internationales.; nationalism.; international relations.; POLITICAL SCIENCE -- Political Ideologies -- Nationalism.; International relations; Nationalism; Nacionalismo.; Nationalisme -- Histoire.